CHATGPT IN ACADEMIC LEARNING: EFL SENIOR COLLEGE STUDENTS’ ATTITUDES AND GENDER DIFFERENCES TOWARD CHATGPT - Fauzi, Chandra; Denashurya, Nugra Irianta; Rahmani, Eka Fajar (The Journal Of English Teaching For Young And Adult Learners, 2025)
The adoption of ChatGPT into academic setting could be more prevalent due to its potential in leveraging EFL learners’ language skills. Despite its popularity, the integration of this AI tool in Indonesia within academic setting is still relatively underdeveloped, and taking into account how learners perceive ChatGPT could potentially provide informed decisions before its integration. Thus, this study aimed at investigating learners’ attitudes towards ChatGPT with particular attention to gender and related variables suggested by the literature. Adopting a qualitative approach through cross-sectional survey, 70 EFL college students of non-English major participated in this study in filling out five-likert scale of 32 items. The findings demonstrated that learners had moderate attitude towards ChatGPT in behavioral, affective, and emotional aspect, and exhibited low frequency and usage duration on ChatGPT. The students had mixed attitudes on ethical issues in using ChatGPT, and generally supported the notion of using ChatGPT adhering to institution regulation, and there was no indication of addition to the tool in academic setting. While there was no significant difference in affective and cognitive aspects, it was found that male differed significantly than female students in terms of behavioral aspect, indicating the tendency of using ChatGPT for future academic activities.